AS ORGANIZAÇÕES E O TURISMO SUSTENTÁVEL: UMA ANÁLISE NO CONTEXTO DO CÓDIGO DE ÉTICA E CONDUTA AMBIENTAL DA ASSOCIAÇÃO ROTEIROS DE CHARME NO BRASIL - Maria Caroline Moron Urt (2017)
Although regulatory, corporate and technological measures generates important outcomes to the impacts of tourism, exploring the individual and organizational meanings and actions in face of ethical responsibility to the environment and the sustainable use of resources may raise unexplored questions of the subject, and new approaches might be considered at the organizational level. This content analysis constitutes an essentially qualitative research, a case study, descriptive and exploratory study aimed to analyze the organizations' sustainable behavior under the optics of substantive and instrumental rationality, having as object of study a Code of Ethics and Environmental Conduct which guides hotels affiliated with a private nonprofit association. Specifically, it is intended to: i) identify the predominant type of rational action in the construction of the Code of Ethics and Environmental Conduct; ii) characterize the meanings and senses related to sustainability that have guided organizations members through the code of ethics and environmental conduct; iii) evaluate the adherence of the code of ethics and environmental conduct in face of the international policies for sustainable development in the field of sustainable tourism. Semi-structured interviews were applied to the members of the Roteiros de Charme Association and the interviews were transcribed and analyzed through content analysis techniques, and compared with the document analysis according to the pre-defined analytical categories. Substantive characteristics such as autonomy, understanding, emancipatory values and ethical judgment were verified, and in the instrumental scope the meanings of calculation, ends, success and results were verified. The presence of ethical judgment guarantees the predominance of substantive rational action in the context of the Code of Ethics and Environmental Conduct, in addition, it was also observed that it is related to the objectives for Sustainable Tourism and contributes to the development of sustainable actions in the Organizations. The diversity of ethical forms present in the elaboration of the Code of Ethics and Environmental Conduct, allied with the substantive and instrumental characteristics of the rational action and the affectivity in relation to the Environment generated an ethics focused on sustainability in the analyzed context, thus this research provides new approaches and insights regarding the sustainability, ethical and socio-environmental responsibility of tourism organizations.